Response of Partly Recrystallized Microstructure to the Rapid Heat Treatment in TC18 Alloy - Fucheng Qiu; Orest Ivasishin; Shucheng Dong; Tuo Cheng; Dmytro Savvakin; Xinlin Li (Advances in Materials Science and Engineering)
The response of TC18 (Ti-5Al-5Mo-5V-1Cr-1Fe) alloy bar to the rapid heat treatment (20 K•s−1) in the 850 to 950°C temperature range followed by ageing at 500°C for 8 hours was studied in this paper. Starting material was only partly recrystallized; share of nonrecrystallized part was not uniform along the bar and consisted 10 to 50% of the cross section. Although both parts, recrystallized and nonrecrystallized, had α+β phase composition, the morphology of a phase in them was different. Due to that and, presumably, to different defect density, the two parts behaved differently upon rapid heating and ageing keeping the properties fluctuated depending on the fraction of the nonrecrystallized part in the particular specimen since nonrecrystallized material remained harder and stronger and therefore more inclined for microcracks to nucleate and grow. Such fluctuation masked a possible temperature dependence of the properties. It resulted in a strength level of around 1700 MPa which is well above the typical strength of this alloy achieved with conventional thermal hardening. Thus, rapid heat treatment can be successfully used to process an extremely high strength condition in titanium alloys to increase their competitiveness in many attractive applications.